Extracting Appalachia : images of the Consolidation Coal Company, 1910/1945 - Buckley, Geoffrey L., 1965- (Ohio University Press, 2004)
Annotation "The Consolidation Coal Company, one of the largest coal-mining operations in the United States during the first half of the twentieth century, had photographers take hundreds of pictures of nearly every facet of its operations." "Historical geographer Geoffrey L. Buckley examines the company's photograph collection housed at the Smithsonian Institution's National Museum of American History. Included in the collection are images of mine openings, mining equipment, and mine accidents, as well as scenes of the company towns, including schools, churches, recreational facilities, holiday celebrations, and company stores."--BOOK JACKET. Title Summary field provided by Blackwell North America, Inc. All Rights Reserved.